Genome-wide investigation and expression analysis of sweet cherry PavNAC gene family under different abiotic stress - Shi, Xiaomeng; Ai, Xianyang; Tian, Changping; Zhang, Aidi; Li, Jianzhao; Sun, Shuyang (Frontiers in Plant Science, 2025)
The NAC gene family is an important transcription factor unique to plants, widely involved in plant growth, development, and response to different stress. The physicochemical properties, phylogenetics, chromosome localization, gene structure and motif, collinearity, and gene expression under stress of the PavNAC transcription factor family in sweet cherry were analyzed. The results showed that the whole genome sequence of sweet cherry contains 132 PavNAC transcription factor genes, which are unevenly distributed on 8 chromosomes and divided into 10 subfamilies. The protein length of PavNAC ranged from 152 to 755 amino acids, and the CDS length ranged from 459 to 2268. The gene structure showed that most PavNAC members contain 3 exons and 10 motifs. Collinearity analysis result showed that 54 PavNAC genes in sweet cherry have homologous genes in Arabidopsis. Transcriptome data of different development stages of ‘Hong Deng’ and ‘Black Pearl’ showed that PavNAC42 and PavNAC101 were specifically expressed in both varieties. Finally, expression of 15 PavNAC genes under different abiotic stress were analyzed by real-time PCR. The results showed that PavNAC70, PavNAC9, and PavNAC10 were induced by low temperature. PavNAC70 and PavNAC81 were both induced by salt and PEG stresses. The study laid the foundation for subsequent molecular breeding and further exploration of the function of PavNAC genes in sweet cherry.